New neoadjuvant treatment strategies for gastric and gastroesophageal junction cancers - (:unkn) unknown (My University, 1999)
Objective: The feasibility of neoadjuvant chemotherapy for clinically unresectable gastric and gastroesophageal (GE) junction cancers. Methods: Eleven patients with gastric and GE junction cancers underwent preoperative combined modality chemo and radiotherapy and a subsequent attempt for surgical resection. Results: Combined modality periadjuvant therapies downsized 9 of 11 T3-4 gastric and gastroesophageal junction cancers and produced 4 pathologically proven complete remissions. Treatment appeared to convert lymph nodes to a cancer free status for 7 of 11 patients. After treatment, exploratory surgery found that 3 patients had only minute foci of occult metastatic disease. The quality of the responses was underestimated by both endoscopic ultrasound and CT scans. Responses were sometimes only achieved after 2-3 months of therapy. Conclusion: Combined modality therapy demonstrates the feasibility of a flexible multistep approach to neoadjuvant therapy incorporating new drugs such as methotrexate and hydroxyurea in addition to fluorouracil and cisplatin. Long delays in surgery (gastrectomy) appear to be safe in the context of combined modality therapy. Median survival exceeds 2 years. The experience suggests new early end points for evaluation of neoadjuvant treatments: quality of life, quality of lymph node sterilization and extent of required gastrectomy in comparison to standard surgery.
Keywords: Combined modalit treatment; Gastric cancer; Gastroesophageal cancer; Neoadjuvant